1999
DOI: 10.1007/s100530050470
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reactive nucleation of silver and alkali clusters in the presence of oxygen and water

Abstract: The nucleation of silver-atom vapor in the presence of O 2 and H 2 O molecules has been investigated by photoionization mass spectrometry and compared to the case of alkali-atom vapor. Relative intensities in mass spectra show that silver vapor does not react with H 2 O molecules, in contrast with sodium vapor. When O 2 and H 2 O are simultaneously present, hydroxided products are observed. Results emphasize the role of stable units, (NaOH) 2 or (KOH) 2 , for alkalies, and more complex hydrated or hydroxided s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The blue solid curve shows the mobility distribution measured at purified conditions with significantly lower water and oxygen levels compared to the non-purified case (ppb levels). Earlier studies have shown that water does not react with silver clusters in the absence of oxygen (Br echignac et al 1999a). As a result, the elimination of most peaks of the cluster mobility distribution can be attributed to etching by O 2 .…”
Section: Effect Of Gas Puritymentioning
confidence: 88%
“…The blue solid curve shows the mobility distribution measured at purified conditions with significantly lower water and oxygen levels compared to the non-purified case (ppb levels). Earlier studies have shown that water does not react with silver clusters in the absence of oxygen (Br echignac et al 1999a). As a result, the elimination of most peaks of the cluster mobility distribution can be attributed to etching by O 2 .…”
Section: Effect Of Gas Puritymentioning
confidence: 88%
“…The vapor of cuprous halides CuCl, CuBr, CuI contains mainly trimers but also tetramers [1][2][3][4], whereas monomers and dimers are roughly equally abundant in the vapors of AgCl, AgBr and AgI [5]. It has also been demonstrated that the trimer is a building block in silver hydroxide clusters [6][7][8]. Another common point is the iono-covalent nature of bonding in both cuprous and silver halides.…”
Section: Introductionmentioning
confidence: 94%
“…Surprisingly, while several studies of water adsorption have been performed on clusters of other transition metals, [35][36][37][38][39] almost none have been carried out on gas-phase gold species. To date, the only studies in the gas phase have concerned the binding of water molecules to the Au 1 monomer cation.…”
Section: Introductionmentioning
confidence: 99%